The Influence of Replacing Sand with Waste Glass Particle on the Physical and Mechanical Parameters of Concrete - Dabiri, Hamed; Sharbatdar, Mohammad Kazem; Kavyani, A.; Baghdadi, M. (Civil Engineering Journal, 2018)
Glass is a special type of materials which is widely used in various forms and colors for different usages. Colored bottles comprise a large part of waste glass. To reduce the destructive effects of waste glass on the environment, it might be recycled. However, some indecomposable waste materials are buried. This will have harmful effects on the environment. A practical solution for reducing non-recyclable waste colored glass is using them as replacements for materials in other industries such as concrete industry. The effect of replacing aggregate with waste glass particle on the compressive strength and weight of concrete is investigated in this study. To achieve the goal, totally 27 cubic specimens were created; 6 specimens were made of concrete, while waste glass particle was added to the mix of other specimens. To prevent Alkali Silica Reaction (ASR), Microsilica was added to the mix of specimens containing glass. Generally, Results indicated that replacing aggregate with glass particle more than 30% lead to increment in compressive strength of concrete. The weight of concrete remains almost the same in all of the specimens. Briefly, based on the results it could be concluded that the optimum percentage for replacing aggregate with glass particle is 50%.